FLUORESCENCE CHARACTERISTICS OF FLUORESCEIN AND EOSIN Y SOLUTIONS IN WATER-MICELLAR SURFACTANT MEDIA: DOI: https://doi.org/10.17721/1728-2209.2020.1(57).6 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
The effect of cationic, anionic and nonionic surfactants on the fluorescence properties of fluorescein and eosin Y aqueous solutions has been investigated. It has been found that sodium dodecyl sulfate does not affect the position of the maximum wavelengths of solutions of fluorescein and eosin Y in the study of the effect of an anionic surfactant on the fluorescence emission intensity of dyes. The intensity of the signal of the dye solutions when changing the concentration of anionic surfactant changes little. As the concentration of non-ionic surfactant increases, the fluorescence emission intensity of the fluorescein solutions decreases. In contrast, with increasing concentration of Triton X-100, there is an increase in the signal intensity of solutions of more hydrophobic eosin Y with subsequent access to the "plateau" at СТХ‑100≥5.1 · 10–2 mol/L. The position of the maxima fluorescence emission wavelengths for the fluorescein solutions in the 0‑1.0 · 10–5 mol/L range of concentrations of cationic surfactant cetylpyridinium chloride remain unchanged. The position of the maxima shifts to the long-wavelength region of the spectrum at higher concentrations of CPC. The nature of the position dependence of the fluorescence emission maxima of eosin Y solutions in the presence of cationic surfactants is similar. The effect of fluorescence quenching has also been shown in the study of the influence of organic substances of cationic nature on the signal intensity of fluorescein solutions. It has been shown that the concentration dependence is linear in the 1.0·10‑2–4.0 · 10–1mol/L range of isoniazid molecule concentrations. The data obtained can be implemented in the development of conditions and methods for the determination of pharmacologically active substances of cationic nature by reaction with fluorescein in medicines.
Keywords: fluorescence, surfactant, fluorescein, eosin Y.